PENINGKATAN KREATIVITAS PEMASARAN DAN KUALITAS NETWORKING BERBASIS ORIENTASI PASAR TERHADAP KINERJA PEMASARAN (Studi Kasus pada CV. Mubarokfood Cipta Delicia Kudus) - Alfiatur Rohmaniyah; Tatiek Nurhayati (Jurnal Ekonomi dan Bisnis, 2017)
The purpose of this research is to examine and analyze the effect of market orientation onperformance marketing on the CV. Cipta Delicia Mubarokfood Holy marketing creativity andnetworking as an intervening variable. The population is all employees of marketing and salesdistribution in the CV. Copyright Mubarokfood Holy Delivia by 92 employees. Given a populationof only 92 employees, it deserves to be taken as a whole to be sampled, so this study is a censusstudy. A tool of analysis is path analysis, which previously tested the validity and reliability.The test results indicate that the market orientation proved to have significant positive effecton marketing creativity, quality networiking and marketing performance. Creativity marketingto become an intervening variable between market orientation on performance marketing,meaning that the higher the market orientation, such as by looking at the frequency of meetingswith customers, interaction with customers, talk about the tactics and strategies of competitors,convened a meeting to discuss market developments, as well as responsive to changes the priceof competitors, the company can know, understand and address the needs and expectationsof customers, so it takes creativity to improve the performance of the company’s marketingto the fullest. Quality networking is also proven to be an intervening variable between marketorientation on performance marketing, meaning that the higher market orientation, the companycan know, understand and address the needs and expectations of customers, so it takes thequality of good networking in connecting with one another in improving performance marketing.Keywords : market orientation, marketing creativity, quality networking and marketingperformance.